Բառապաշարի շերտերի ոճական բնութագիրը Անդրանիկ Ծառուկյանի արձակում - Մերի Գիվարգիզյան (ՀՀ ԳԱԱ հրատ.)
The study of a language and style of a literary work begins from the lexicological level of the language, that is from the analysis of the vocabulary. In this article is studied the layer of the vocabulary of Andranik Tsarukyan's prose, especially dialectical and Old Armenian words, barbarisms, their stylistic role and meaning in author's and hero’s speech.
Keywords: Philology; Linguistics; Language and Literature